Resource allocation for full‐duplex–based heterogeneous cellular networks considering back‐haul capacity - Mardi, A.; Azmi, P.; Mokari, N.; Parsaeefard, S. (Transactions on emerging telecommunications technologies, 2017)
In this paper, we propose a heterogeneous cellular network based on orthogonal frequency division multiple access consisting of full‐duplex femtorelays. Then, we design schemes for the uplink radio resource allocation. The goal of the proposed schemes is to maximize the sum rate, taking into account the back‐haul and transmission power constraints. Moreover, the superiority of the proposed system is shown by comparing it with the half‐duplex femtorelay‐assisted counterpart. Since the proposed resource allocation optimization problem is nonconvex and intractable, we divide it into subcarrier and transmission power allocation subproblems and then use an iterative algorithm to solve each of them. Toward this end, in each iteration, subcarriers are allocated via a binary linear program, while the successive convex approximation method is adapted to transform the nonconvex transmission power allocation subproblem into a sequence of convex subproblems. To achieve this goal, we use 1 of the 3 proposed approaches, namely, dual, arithmetic‐geometric mean approximation, and difference of 2 concave functions. In addition, we investigate the performance, convergence, and computational complexity of these approaches. The simulation results reveal that the proposed approaches are close to the optimal solution while providing less computational complexity. Moreover, they illustrate that even by considering self‐interference in the full‐duplex mode, the sum rate will be increased approximately by 41% in comparison with the half‐duplex mode. In this paper, we concentrate on the resource allocation of the full‐duplex femtorelays with limited back‐haul capacity links in an OFDMA‐based heterogeneous cellular network. The considered objective is to maximize the sum rate of all users and small cells, subject to transmission power limitation and also back‐haul capacity constraint. Because the corresponding optimization problems were nonconvex with high‐computational complexity, we used the SCA method with 3 approaches, namely, dual, DC, and AGMA.